UV Spectrophotometric Determination of Ioratadine in Tablets - SARAVANAN, V.S.; KUMAR KATIYAR, PRASHANT (Asian Journal of Chemistry, 2010)
Simple, sensitive and economical UV spectrophotometric method is developed for the estimation of loratadine in tablets. In this method, loratadine is determined accurately having absorbance maximum at 246 nm. Beer’s law is obeyed in the concentration range 0-25 μg. Linearity is obtained in the concentration range of 5-25 μg/mL.